1993
DOI: 10.1095/biolreprod49.3.483
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Serum Immunoreactive Inhibin-α during Photoperiod-Induced Testicular Regression and Recrudescence in the Golden Hamster1

Abstract: Serum immunoreactive inhibin-alpha (irI alpha), FSH, LH, and testosterone (T) were measured in male golden hamsters during short-day-induced testicular regression and during testicular recrudescence following the transfer from short to long days. Serum FSH levels were maximally suppressed within 2 wk of transfer to short days. In contrast to FSH, irI alpha levels were not fully reduced until after 6 wk of exposure to short days, closely paralleling the timing of testicular regression. LH and T levels were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
17
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 0 publications
7
17
0
Order By: Relevance
“…This has also been demonstrated for the males of other seasonal breeders such as sheep [15], monkeys [16] and hamsters [17]. The annual change in circulating inhibin pro-αC levels in the present study showed a positive correlation with ir-inhibin, testosterone and estradiol-17β indicating that circulating concentrations of inhibin pro-αC reflect the seasonal testicular function of stallions.…”
Section: Discussionsupporting
confidence: 85%
“…This has also been demonstrated for the males of other seasonal breeders such as sheep [15], monkeys [16] and hamsters [17]. The annual change in circulating inhibin pro-αC levels in the present study showed a positive correlation with ir-inhibin, testosterone and estradiol-17β indicating that circulating concentrations of inhibin pro-αC reflect the seasonal testicular function of stallions.…”
Section: Discussionsupporting
confidence: 85%
“…In the immature rat testis, altered thyroid status has marked effects on Sertoli cells proliferative capacity and differentiation leading to modifications in testis size, Sertoli cells number and sperm production in adult life (Wagner et al, 2008). These T3 effects, initially described in rodents Joyce et al, 1993;Kirby et al, 1993), were subsequently identified in different vertebrate species (Jannini et al, 1995;Jansen et al, 2007;Kirby et al, 1996;Majdic et al, 1998;Matta et al, 2002;Weng et al, 2007).…”
Section: Actions Of Thyroid Hormone On Testismentioning
confidence: 99%
“…The facility is located in the northern part of Japan (N 40°, E 140.4°) and consists of an outdoor run where the animals can The testis of seasonal breeders including bear species exhibits morphological differences throughout the year [6,7,11,14,19]. It has been reported that spermatogenic activity exhibited seasonal changes accompanied by changes in peripheral concentrations of testosterone [11,12,14,19,20,24,38]. These findings strongly suggest the occurrence of seasonal changes in testicular steroidogenesis in seasonal breeders such as bears.…”
Section: Animalsmentioning
confidence: 99%